Staged Endovascular Repair of Isolated Bilateral Internal Iliac Artery Aneurysms: A Case Report - Maltezos, Chrisostomos; Galyfos, George; Kerasidis, Stavros; Geropapas, Georgios; Makris, Nikolaos (International Journal of Angiology, 2016)
This report aims to present an unusual case with isolated bilaterally located internal iliac artery aneurysms (IIAAs) that were incidentally detected. Owing to the high surgical risk of the patient and anatomical location of the aneurysms, an endovascular management was preferred. Initially, the patient underwent a percutaneous embolization of the right-sided aneurysm with coiling. A stent-graft deployment covering the orifice of the left-sided internal iliac artery and occluding the ipsilateral aneurysm followed 1 month later. The patient remains asymptomatic after 6 months. Endovascular management has been associated with lower morbidity and hospital stay compared with open repair for IIAAs, although both techniques show satisfying early and mid-term results. Especially for bilaterally located aneurysms, a staged strategy decreases the risk for ischemic complications. Finally, endovascular methods should be preferred when there are no compression symptoms or in cases of higher surgical risk.
Keywords: bilateral; internal iliac artery; aneurysm; endovascular; coiling